Analysis of polymorphisms in the merozoite surface protein-3a gene and two microsatellite loci in Sri Lankan Plasmodium vivax: evidence of population substructure in Sri Lanka - Schousboe, M.L.; Rajakaruna, R.S.; Amerasinghe, Priyanie H.; Konradsen, Flemming; Ord, R.; Pearce, R.; Bygbjerg, C.; Roper, C.; Alifrangis, M. (American Society of Tropical Medicine and Hygiene, 2011)
The geographical distribution of genetic variation in Plasmodium vivax samples ( N = 386) from nine districts across Sri Lanka is described using three markers; the P. vivax merozoite surface protein -3a ( Pvmsp -3a) gene, and the two microsatellites m1501 and m3502. At Pvmsp -3a, 11 alleles were found with an expected heterozygosity (H e ) of 0.81, whereas at m1501 and m3502, 24 alleles (H e = 0.85) and 8 alleles (H e = 0.74) were detected, respectively. Overall, 95 unique three locus genotypes were detected among the 279 samples positive at all three loci (H e = 0.95). Calculating the pairwise fixation index ( F ST ) revealed statistically significant population structure. The presence of identical 2-loci microsatellite genotypes in a significant proportion of samples revealed local clusters of closely related isolates contributing to strong linkage disequilibrium between marker alleles. The results show evidence of high genetic diversity and possible population substructure of P. vivax populations in Sri Lanka.